Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s13277-015-3742-2
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic effects of Rhodiola crenulata treatment on B16-F10 melanoma

Abstract: Melanoma is an aggressive form of skin cancer with limited treatment options for advanced stage disease. Early detection and wide surgical excision remain the initial mode of treatment for primary tumors thus preventing metastases and leading to improved prognosis. Through this work, we have evaluated the antineoplastic effects of Rhodiola crenulata (R. crenulata) root extracts on the B16-F10 melanoma cell line, both in vitro and in vivo. We observed that R. crenulata treatment resulted in increased cell death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Talin regulates the stability of E-cadherin transcriptional repressors [58]. An increased expression of E-cadherin was observed after reducing the level of β 1 -integrin in B16-F10 melanoma cells [59]. Treatment with recombinant MMP-9 or transient expression of MMP-9 is sufficient to reduce E-cadherin levels in differentiated ovarian tumor cells [60].…”
Section: Discussionmentioning
confidence: 99%
“…Talin regulates the stability of E-cadherin transcriptional repressors [58]. An increased expression of E-cadherin was observed after reducing the level of β 1 -integrin in B16-F10 melanoma cells [59]. Treatment with recombinant MMP-9 or transient expression of MMP-9 is sufficient to reduce E-cadherin levels in differentiated ovarian tumor cells [60].…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer activity of another R. crenulata extract (Extract 6 ) has been investigated on U87 GBM cells, which involves the inhibition of Wnt​‐β‐​catenin signaling . In addition, Extract 8 could induce cell death and antiproliferation effect in B16‐F10 mouse melanoma cells, and inhibit metastatic melanoma in a mouse model . A 96% ethanol extract of R. rosea (Extract 9 ) could induce apoptosis and necrosis in HL‐60 cells by cell cycle arrest in G1 phase .…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…143 In addition, Extract 8 could induce cell death and antiproliferation effect in B16-F10 mouse melanoma cells, and inhibit metastatic melanoma in a mouse model. 145 A 96% ethanol extract of R. rosea (Extract 9)…”
Section: Anticancer Activitymentioning
confidence: 99%
“…In this study, we found that ICA could inhibit cell proliferation and reduced colony formation in a concentration- and time-dependent manner. This is important because uninhibited migration of melanoma leads to aggressive phenotype and high mortality rates of patients [ 20 ]. So, we carried out further experiments to explore the mechanism of ICA on B16 cell proliferation.…”
Section: Discussionmentioning
confidence: 99%